On the nature of the Cape Folding, by analysis of a structural section between Towerwaterpoort and Strydomsvlei, district Willowmore, C.P. - Theron, J. N. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 1960.